(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
Conversion of sucrose into fructose and gluconic acid using invertase, glucose oxidase and catalase was studied by discontinuous (sequential or simultaneous addition of the enzymes) and continuous (simultaneous addition of the enzymes in a 100 kDa-ultrafiltration membrane reactor) processes. The following parameters were varied: concentration of enzymes, initial concentration of substrates (sucrose and glucose), pH, temperature and feeding rate (for continuous process). The highest yield of conversion (100%) was attained through the discontinuous (batch) process carried out at pH 4.5 and 37 ºC by the sequential addition of invertase (14.3 U), glucose oxidase (10,000 U) and catalase (59,000 U).